Compressive properties of a novel additively manufactured 3D auxetic structure. (1st July 2019) - Alomarah, Amer; Ruan, Dong; Masood, Syed; Gao, Zhanyuan
Abstract: A novel 3D re-entrant chiral auxetic (RCA) structure has been proposed for the first time in this study. The unit cell has been developed with solid cubes and struts based on the topological features of both re-entrant honeycomb and chiral honeycomb. A recently developed powerful 3D printing process, Multi Jet Fusion (MJF), has been employed to print six samples from polyamide 12 (PA 12). Uniaxial quasi-static compressive tests have been performed in the X, Y and Z directions to investigate the deformation, Poisson's ratio and energy absorption of the proposed structure. Finite element (FE) models have been developed using ANSYS/LS-DYNA and verified by the respective experimental data. The experimental microscopic measurements reveal high accuracy of MJF process to produce robust parts with smooth internal morphology. The designed cubes are found to demonstrate a similar rotation function to that of cylinders of the corresponding 2D RCA structure. The plastic bending and buckling are found to be the dominated deformation mechanisms for the samples compressed in the Y direction, while plastic bending is the dominated deformation mechanism for the samples compressed in the X and Z directions. The proposed structure displays auxetic feature under uniaxial compression in all three directions, which facilitates a more severe compaction of the structure and results in an improved load carrying capacity. It is also found that the compressed RCA structure when loaded in the X direction outperforms in terms of auxeticity and energy absorption compared with the other (Y and Z) directions. The proposed 3D RCA structure has anisotropic properties.